Skin immune response of rainbow trout (Oncorhynchus mykiss) experimentally exposed to the disease Red Mark Syndrome - von Gersdorff Jørgensen, Louise; Schmidt, Jacob Günther; Chen, Defang; Kania, Per Walter; Buchmann, Kurt; Olesen, Niels Jørgen (Veterinary immunology and immunopathology, 2019)
•Red Mark Syndrome (RMS) was transferred to naïve specific pathogen free fish.•Lesions in the skin showed a Th1-type profile using gene expression.•The same lesions showed a high expression of IgD, IgM and IgT.•Results support that MLO causes RMS.•Fish overcome the infection with a Th1-type response supplemented by antibodies. Red Mark Syndrome (RMS) is a skin disease reported from farmed rainbow trout. Since the turn of the millennium it has been spreading through Europe. RMS is probably a bacterial disease caused by a Midichloria-like organism (MLO). It is non-lethal and causes little obvious changes in appetite or behavior but results in red hyperaemic skin lesions, which may lead to economic losses due to downgrading. Here we transfer RMS to naïve specific pathogen free (SPF) fish by cohabitation with RMS-affected seeder fish. During disease development we characterize local cellular immune responses and regulations of immunologically relevant genes in skin of the cohabitants by immunohistochemistry and qPCR. Skin samples from SPF controls and cohabitants (areas with and without lesions) were taken at 18, 61, 82 and 97 days post-cohabitation. Gene expression results showed that lesions had a Th1-type profile, but with concurrent high expression levels of all three classes of immunoglobulins (IgD, IgM and IgT). The marked local infiltration of IgD + cells in the skin lesions as well as a highly up-regulated expression of the genes encoding sIgD and mIgD indicate that this immunoglobulin class plays an important role in skin immunity in general and in RMS pathology in particular. The co-occurrence of an apparent B cell dominated immune reaction with a Th1-type profile suggests that the local production of antibodies is independent of the classical Th2 pathway.